2021
DOI: 10.1038/s43018-021-00191-y
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of seroconversion for SARS-CoV-2 IgG in patients with malignant disease and association with anticancer therapy

Abstract: Patients with cancer have been identified in several studies to be at high risk of developing severe COVID-19; however, rates of SARS-CoV-2 IgG seroconversion and its association with cancer types and anticancer therapy remain obscure. We conducted a retrospective cohort study in patients with cancer who underwent SARS-CoV-2 IgG testing. Two hundred and sixty-one patients with a cancer diagnosis underwent SARS-CoV-2 IgG testing and demonstrated a high rate of seroconversion (92%). However, significantly lower … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
85
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 28 publications
10
85
1
3
Order By: Relevance
“…In a study of 261 patients with cancer, Thakkar et al showed the signi cantly lower seroconversion observed in patients with hematological malignancy after Covid-19 infection, particularly in patients exposed to anti-CD20 antibody containing therapy [5]. B-cell depletion by treatment with rituximab or obinutuzumab can also cause suppression of the immune response to vaccines [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 261 patients with cancer, Thakkar et al showed the signi cantly lower seroconversion observed in patients with hematological malignancy after Covid-19 infection, particularly in patients exposed to anti-CD20 antibody containing therapy [5]. B-cell depletion by treatment with rituximab or obinutuzumab can also cause suppression of the immune response to vaccines [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Notably the anti-S IgG seroconversion rates were lower or less pronounced in patients with a hematological conditions, in particular in patients treated with highly immune suppressive therapy, such as stem cell transplantation, anti-CD20 therapy or chimeric antigen receptor (CAR)-T cell therapy. 12 Small cohort studies have reported low seroconversion rates following a single dose of mRNA vaccination in the UK and France and seropositivity rates in patients with CLL and multiple myeloma. 13,14 Within our cohort of 131 patients, the overall seropositivity rate was 81% after the rst dose and up to 94% at 4 weeks after the second dose.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of virus is higher in people who develop severe or critical illness ( 55 , 56 ). In few severely immunocompromised patients, especially haematological patients with B-cell defect due to the underlying disease or treatment with anti-CD20 antibody, active viral replication can be detected weeks to months after symptom onset ( 57 , 58 ). The same patient population has an increased risk of severe COVID-19.…”
Section: Oseltamivir Is Given On Suspicion Of Influenzamentioning
confidence: 99%
“…Patients after a severe case of COVID-19 should be evaluated individually in regard to the duration of isolation. Immunosuppressed individuals, in particular patients with impaired B-cell function ( 57 , 58 , 62 ), may excrete contagious virus for a prolonged time periode, hence ceasing isolation may require expert consultation. Patients can be discharged with or without isolation after recovery of acute symptoms.…”
Section: Dischargementioning
confidence: 99%